Meningkatkan Keterampilan Berpikir Kritis Siswa Pada Muatan IPA Menggunakan Model Group Investigation - Tarisya Herdayanti; Tika Puspita Widya Rini (CV. ITTC INDONESIA, 2024)
Education serves as a conduit for students to cultivate their abilities in problem-solving within the context of daily life through the process of learning. Nevertheless, the current conditions in the field do not align with this expectation. Researchers have seen that certain pupils exhibit a deficiency in their capacity to recognise problems, produce ideas, and effectively absorb the information they are presented with. The objective of this study was to enhance students' critical thinking abilities through the implementation of the Group Investigation paradigm. The research was carried out at SDN Kebun Bunga 6 Banjarmasin, including a total of 19 grade V pupils. This study employs a qualitative research approach, specifically utilising the classroom action research method, which involves doing four sessions of data collection. The study's findings demonstrate a consistent improvement in students' critical thinking abilities throughout each meeting. Specifically, during meeting 1, 47% of students were classified as